Revisiting Racialized Voice : African American Ethos in Language and Literature. - Holmes, David G. (Southern Illinois University Press, 2007)
Revisiting Racialized Voice: African American Ethos in Language and Literature argues that past misconceptions about black identity and voice, codified from the 1870s through the 1920s, inform contemporary assumptions about African American authorship and ethos. Tracing elements of racial consciousness in the works of Frederick Douglass, Charles Chesnutt, W.E.B. DuBois, Zora Neale Hurston, and others, David G. Holmes urges a revisiting of narratives from this period to strengthen and advance notions about racialized writing and to shape contemporary composition pedago.